PERTANGGUNGJAWABAN PIDANA KORPORASI PADA KJPP MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Hamidi, Dudung; Ratnawati Gultom, Elfrida (Universitas Ekasakti, 2023)
Law Number 1 of 2023 concerning the criminal code in articles 12, 20, 36, as well as in articles 45 to 50, states that corporations have legal responsibilities where the corporation is a business entity or not a legal entity in the form of a firm, limited partnership or equivalent according to law legislation. One of the business entities is the Office of public appraisal service (KJPP) was formed based on the regulation of the Minister of Finance number 228/PMK.01/2019. The research is a descriptive analysis research using a normative juridical and references in the form of legislation and literature that supports the research. The purpose of the research is to analyze the existence of corporate responsibility for KJPP to Law number 1 of 2023 and legal protection in carrying out appraisal professional service activities. The results of the analysis show that until recently: (1) KJPP is directly related to corporate criminal responsibility and (2) its activities of KJPP does not currently have good legal protection because in carrying out the appraisal profession it is still supported by a Ministerial of Finance Regulation which hierarchically, legislation are at the bottom.